The “Epilepsy and Paroxysmal Conditions” Journal Founder’s and Publisher's Statement - E. V. Dizhevskaya; D. V. Blinov (Эпилепсия и пароксизмальные состояния, 2023)
The Founder and Publisher became aware of a potential apparent conflict of interest – it is assumed that it is not entirely correct to continue to be the Editor-in-Chief at the “Epilepsy and Paroxysmal Conditions” Journal, being a member of the founders of an organization that has registered another journal with similar name. Therefore, the Founder of the “Epilepsy and Paroxysmal Conditions” Journal was forced to refuse further cooperation with the Editor-in-Chief. Information about a new Editor-in-Chief will be brought in a separate order. Also, informational support of any public organizations by the journal is suspended until the situation is clarified. The entire cycle of editorial processes is now fully controlled by the Irbis LLC. No changes in the operating team occurred. The “Epilepsy and Paroxysmal Conditions” Journal continues to be published as usual.